Environmental impacts of different dairy farming systems in the Po Valley. (20th January 2016) - Battini, F.; Agostini, A.; Tabaglio, V.; Amaducci, S.
Abstract: An environmental Life Cycle Assessment (LCA) was performed to compare four typical milk production systems of the Po Valley: drinking milk (A); Parmigiano-Reggiano more intensive (B); Parmigiano-Reggiano less intensive (C) and Grana Padano (D). The input and output data were collected directly from the farmers by way of questionnaires. The results indicated that the total GHG emissions from the analysed farms, with biological allocation, were: 1.47, 1.35, 1.49 and 1.50 kg CO2 eq. kg −1 FPCM (Fat Protein Corrected Milk) for farm A, B, C and D respectively. Excluding Land Use Change (LUC) emissions and Soil Organic Carbon (SOC) sequestration, total GHG emissions were reduced to 1.02, 1.11, 1.26 and 1.20 kg CO2 eq. kg −1 FPCM for farm A, B, C and D respectively. These reductions were mostly due to the GHG emissions associated to the LUC from imported soybean meal, while the contribution of SOC sequestration to the total GHG emissions was found to be negligible. When LUC emissions from imported soybean meal were not included in the analysis, lower GHG emissions were associated to higher milk yield, feed self-sufficiency and feed efficiency. However, when LUC emissions were included in the analysis, the highest level of these parameters did not always lead to a reduction of the total GHG emissions because the higher use of maize silage was associated with an increase in the use of imported soymeal. The results of this LCA also indicated that marine eutrophication, freshwater eutrophication, non-renewable energy use, land occupation and total biodiversity loss decreased as the level of intensification of the production system increased. Conversely, local biodiversity loss, instead, increased if the milk yield per cow increased. We can conclude that, in the specific context analysed, the increase in productivity may lead to a trade-off between global impacts (such as GHG emissions) and local impacts (e.g. local biodiversity and eutrophication). Highlights: A LCA to compare milk production for Parmigiano Reggiano, Grana Padano and drinking milk was carried out. There is a negative correlation between GHG emissions (without LUC emissions) and milk yield. With LUC emissions the increase of milk yield, does not always lead to a reduction of GHG emissions. The increase in milk yield leads to trade-offs between global impacts and local impacts.